2023
DOI: 10.3390/molecules28176251
|View full text |Cite
|
Sign up to set email alerts
|

Spice-Derived Phenolic Compounds: Potential for Skin Cancer Prevention and Therapy

Janette Baloghová,
Radka Michalková,
Zuzana Baranová
et al.

Abstract: Skin cancer is a condition characterized by the abnormal growth of skin cells, primarily caused by exposure to ultraviolet (UV) radiation from the sun or artificial sources like tanning beds. Different types of skin cancer include melanoma, basal cell carcinoma, and squamous cell carcinoma. Despite the advancements in targeted therapies, there is still a need for a safer, highly efficient approach to preventing and treating cutaneous malignancies. Spices have a rich history dating back thousands of years and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 434 publications
0
5
0
Order By: Relevance
“…The use of chili pepper extract caused an inhibition area that was almost three times higher for S. aureus ATCC 25923 than for E. coli ATCC 25922 (Table 4). The antibacterial properties of chili pepper extract may result from the presence of capsaicin in chili fruit and cannabinoids in hemp oil [38,76]. Previous studies have reported that flavonoids and other active components such as capsaicin have potential antibacterial activity [45].…”
Section: Antibacterial Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of chili pepper extract caused an inhibition area that was almost three times higher for S. aureus ATCC 25923 than for E. coli ATCC 25922 (Table 4). The antibacterial properties of chili pepper extract may result from the presence of capsaicin in chili fruit and cannabinoids in hemp oil [38,76]. Previous studies have reported that flavonoids and other active components such as capsaicin have potential antibacterial activity [45].…”
Section: Antibacterial Testsmentioning
confidence: 99%
“…Capsaicin extracted from chili peppers has been reported to have antibacterial and antifungal effects [39]. Chili peppers also contain polyphenols, the healing effects of which were mentioned above [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, and in consideration of the research showing that Hsian-tsao (Mesona chinensis Benth.) extract improves the heat resistance of D. melanogaster, the study of Hsian-tsao has implications for the development of customized inner-beauty and cosmetics products [33][34][35][36]51,52,[101][102][103][104][105][106][107].…”
Section: What Is Already Known About This Topic and What Does This St...mentioning
confidence: 99%
“…The plant's unique fragrance and flavor have made it a desirable ingredient in culinary endeavors worldwide [2]. Beyond its culinary uses, Allspice has a long history of traditional medicinal applications, ranging from digestive aid to pain relief, as well as antibacterial and antioxidant properties [3]. These attributes are due to the diverse range of phytocompounds present in different parts of the plant, including the leaves, bark, and roots [4].…”
Section: Introductionmentioning
confidence: 99%